Comparative study of diffuse midline glioma and glioblastoma: Magnetic Resonance Imaging (MRI) in the characteristics and demography - Joshi, Sabendra; Wu, Yuan-Kui; Xu, Yi-Kai; Liu, Xiao-Min; Zhang, Hao (Nepal Journal of Neuroscience, 2022)
Introduction: Diffuse midline glioma and glioblastoma are classified as grade IV CNS tumors (WHO). The entity ‘diffuse midline glioma, H3 K27 mutant’ was introduced in the 4th revised edition of the 2016 WHO classification of brain tumors; however, there are only a few reports on Magnetic Resonance Imaging of these tumors. Thus, we conducted a retrospective study focused on Magnetic Resonance Imaging features of diffuse midline glioma compared to glioblastoma. This study aims to evaluate and compare the demographic characteristics, anatomic location of lesions, and MRI characteristics of diffuse midline glioma and glioblastoma. Methods: We histologically confirmed 30 patients with diffuse midline glioma and 70 patients with glioblastoma were enrolled in this retrospective study. Pretreatment MRI of each patient was reviewed by a neuroradiology issuing physician and neuroradiology reporting physician for MRI characteristics of tumors. Comparative analysis was performed of the imaging pattern to show differences between diffuse midline glioma and glioblastoma with the p-value. Results: The age of patients with diffuse midline glioma (mean age =24.7 ±10.4) was significantly lower than in those with glioblastoma (mean age =48.2 ±1). The majority of patients with diffuse midline glioma (56.7%) and glioblastoma (51.4%) were ≤ 25 and ≥ 50 years age group respectively. The most common location of diffuse midline glioma and glioblastoma were the thalamus (73.3%) and frontal lobe (37.1%) respectively. The presence of hydrocephalus, edema, and invasion were statistically significantly differences in patients with diffuse midline glioma (hydrocephalus = 46.7%, edema = 53.3%, and invasion =30%) than in those with glioblastoma (hydrocephalus = 12.9%, edema = 88.6%, and invasion =5.7%) (P < 0.05 each). Conclusions: Despite having similar imaging features, diffuse midline glioma exhibited marked differences in age, edema, invasion, and hydrocephalus in MRI compared to Glioblastoma.